How Successful is the Institute of Nursing, Kuwait, in Reducing Dependence on Expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
Imparting knowledge, skills and positive attitude is the core component of technical and vocational education. It is a dual system that permit students, if well organized and monitored, to transfer what they have learned in classroom, laboratories, and workshops into real work environment. It is an opportunity to overcome the shortage of skills in labour market and reduce the rate of unemployment, particularly between youth graduates. Technical and vocational education would not only contribute in reducing the level of unemployment, especially in developing countries, but also in increasing and diversifying productivity, reducing poverty level, maintaining social security and prosperity, decreasing crime rate, and maintaining a stable economic and political status. In the gulf states (e.g., Kuwait, Qatar, Oman), the shortage of indigenous skilled and semi-skilled manpower is highly marked in essential sectors of the economy (oil, electricity and water, infrastructure, health care). As a result, key figures have thoroughly realized the importance of forging technical and vocational institutions to respond to the needs of local industries and business. Kuwait, has realized and appreciate the urgent need of the health sector of highly qualified indigenous specialist and thus established the Institute of Nursing, IN, with the aim to overcome or reduce the level of dependence on expatriates in major hospitals and clinics. The research focuses on identifying and examining the perception of the head of nurses at the health sector towards the standard of the filed training program, and the quality of the Institute of Nursing, IN, graduates. The research is based on extensive field work that encompasses a review of the related literature, interviews with a sample of heads of nurses at the health sector. Finally, the research will argue that unless the IN recognize and appreciate the value of building a strong linkage with the health sector, its contribution in tackling the shortage of skilled and semi-skilled indigenous health care specialist will be below the government expectations, thus continuing relaying on expatriates for years ahead.